The Impact of Creative Thinking Application on Employees’ Performance at Paramilitary Organization - Theeb, Saed Dirar Mohammad (South Asian Journal of Social Sciences and Humanities, 2025)
This study investigates the impact of applying creative thinking on employee performance within paramilitary organizations. In particular, civilian police institutions have demonstrated growing interest in integrating creative thinking as a means to enhance operational efficiency. These organizations have adopted structured policies and decision-making frameworks aligned with innovation-driven training strategies to keep pace with rapid scientific and technological advancements. Effective employee performance in such environments necessitates a foundation of knowledge, coupled with soft and creative skills, within a competency-based training system. A quantitative methodology was employed to assess the influence of creative thinking application on employee outcomes in paramilitary settings. The study focused on a sample of 120 officers from the Palestinian Civil Police. Structural Equation Modeling (SEM) was utilized through the Amos software to analyze the relationship between the key variables. Findings indicate a significant positive effect of creative thinking application on employee performance. This suggests that performance enhancement in paramilitary contexts is closely tied to knowledge acquisition and creative capability development. To maintain service quality and sustain a competitive edge, organizations must assess employee competencies through scientifically grounded standards focused on functional efficiency and innovation.